Occasional human infestations by feral pigeons' ectoparasites: Two case reports. Issue 7 (30th May 2020) - Akhoundi, Mohammad; Brun, Sophie; Marteau, Anthony; Debédat, Jean; Ben Romdhane, Habib; Izri, Arezki
Abstract: Dermanyssus infestation is a rural parasitic problem occurs occasionally in urban areas in people with close contact to pigeons. It can be diagnosed through clinical cutaneous symptoms in exposed body parts, nocturnal itching, and presence of mites in infested locations and can be treated by antiacaricide, environmental, and symptomatic treatments. Abstract : Dermanyssus infestation is a rural parasitic problem occurs occasionally in urban areas in people with close contact to pigeons. It can be diagnosed through clinical cutaneous symptoms in exposed body parts, nocturnal itching, and presence of mites in infested locations and can be treated by antiacaricide, environmental, and symptomatic treatments.